Simulating social-ecological systems: the Island Digital Ecosystem Avatars (IDEA) consortium. Issue 1 (December 2016) - Davies, Neil; Field, Dawn; Gavaghan, David; Holbrook, Sally; Planes, Serge; Troyer, Matthias; Bonsall, Michael; Claudet, Joachim; Roderick, George; Schmitt, Russell; Zettler, Linda; Berteaux, Véronique; et al.
Abstract Systems biology promises to revolutionize medicine, yet human wellbeing is also inherently linked to healthy societies and environments (sustainability). The IDEA Consortium is a systems ecology open science initiative to conduct the basic scientific research needed to build use-oriented simulations (avatars) of entire social-ecological systems. Islands are the most scientifically tractable places for these studies and we begin with one of the best known: Moorea, French Polynesia. The Moorea IDEA will be a sustainability simulator modeling links and feedbacks between climate, environment, biodiversity, and human activities across a coupled marine–terrestrial landscape. As a model system, the resulting knowledge and tools will improve our ability to predict human and natural change on Moorea and elsewhere at scales relevant to management/conservation actions.